Rural community pharmacies’ preparedness for and responses to COVID-19 - Carpenter, Delesha M. (Res Social Adm Pharm, 2021)
BACKGROUND: Few studies have documented rural community pharmacy disaster preparedness. OBJECTIVES: To: (1) describe rural community pharmacies’ preparedness for and responses to COVID-19 and (2) examine whether responses vary by level of pharmacy rurality. METHODS: A convenience sample of rural community pharmacists completed an online survey (62% response rate) that assessed: (a) demographic characteristics; (b) COVID-19 information source use; (c) interest in COVID-19 testing; (d) infection control procedures; (e) disaster preparedness training, and (f) medication supply impacts. Descriptive statistics were calculated and differences by pharmacy rurality were explored. RESULTS: Pharmacists used the CDC (87%), state health departments (77%), and state pharmacy associations (71%) for COVID-19 information, with half receiving conflicting information. Most pharmacists (78%) were interested in offering COVID-19 testing but needed personal protective equipment and training to do so. Only 10% had received disaster preparedness training in the past five years. Although 73% had disaster preparedness plans, 27% were deemed inadequate for the pandemic. Nearly 70% experienced negative impacts in medication supply. There were few differences by rurality level. CONCLUSION: Rural pharmacies may be better positioned to respond to pandemics if they had disaster preparedness training, updated disaster preparedness plans, and received regular policy guidance from professional bodies.